2018
DOI: 10.1039/c8ra03214a
|View full text |Cite
|
Sign up to set email alerts
|

Mussel-inspired bio-compatible free-standing adhesive films assembled layer-by-layer with water-resistance

Abstract: Mussel-inspired, water-resistant, free-standing adhesive films with high transmittance were fabricated with an environmentally friendly layer-by-layer process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 65 publications
1
10
1
Order By: Relevance
“…6-D), which could be justified by the plasticizing effect of PBS [78]. Moreover, the ultimate tensile stress and the Young's modulus decreased in wet conditions comparing to the dry ones, which are in accordance with some findings already reported about the mechanical resistance of some polymeric and composite membranes [82,83] and also regarding the mechanical behavior of commercial resorbable membranes for periodontal regeneration [82,84,85]. In the wet state, formulations containing Ag-BGs (F3 and F4) presented higher Young's modulus values, but for the ultimate strain (ε B ) they presented lower values than the control ones.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…6-D), which could be justified by the plasticizing effect of PBS [78]. Moreover, the ultimate tensile stress and the Young's modulus decreased in wet conditions comparing to the dry ones, which are in accordance with some findings already reported about the mechanical resistance of some polymeric and composite membranes [82,83] and also regarding the mechanical behavior of commercial resorbable membranes for periodontal regeneration [82,84,85]. In the wet state, formulations containing Ag-BGs (F3 and F4) presented higher Young's modulus values, but for the ultimate strain (ε B ) they presented lower values than the control ones.…”
Section: Resultssupporting
confidence: 90%
“…Comparing these results with those presented in a previous work about polysaccharide/BGs FS membranes, where adhesive strength values between 90 and 150 kPa were reported [44], it should be mentioned that the present study exhibited films with enhanced adhesive strength. Moreover, in a more recent work where bioinspired FS adhesive films were developed with chitosan and hyaluronic acid, Wang et al [83] reported similar excellent wet adhesion strength for FS films with 300 layers, reaching the maximum adhesion around 400 kPa. Herein, the polymeric formulation F2 presented higher adhesive strength (448.61 ± 68.07 kPa) followed by the composite formulation F4 (234.55 ± 67.56 kPa), the polymeric formulation F1 (222.02 ± 108.10 kPa) and finally, the composite F3 (202.73 ± 71.19 kPa).…”
Section: Resultsmentioning
confidence: 94%
“…Grafting of catechol to form functional polymers has been a universal study strategy . C and D are often chosen due to their simple structure that can be easily grafted onto polymers, such as grafting of catechol with a carboxyl group or amino group onto polymers with amino and carboxyl groups . These catechol‐functionalized polymers provide an adhesion surface and enable a mechanically robust coating tightly on the surface of intrinsic hydrophobic polymers.…”
Section: Resultsmentioning
confidence: 99%
“…In parallel, biopolymeric films containing catechol groups were also developed as their controls (CTR). Conventional layer-by-layer through dip-coating was chosen for film build-up, since it is simple and versatile methodology to construct thin films with complex architecture and multifunctionalities, allowing to tune the film properties at the nanoscale length [10,11,[39][40][41], being suitable for coating substrates with different compositions, topographies and complex geometries [42,43]. In this study, natural polyelectrolytes were catechol-functionalized as the organic phase in the LbL assembly, aiming to enhance the film stability and improving adhesion strength.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, as positively charged polymer, chitosan is a partially deacetylated derivative from chitin, with known biocompatibility and biodegradability [45,46]. As Wang and coworkers [41] already demonstrated, the catechol functionalization of CHT and HA through carbodiimide chemistry preserved the cationic and anionic characteristics of these polymers, as well as their electrostatic interactions, providing a successful construction free-standing adhesive films. In addition, as Lu et al [47] demonstrated through QCM study, multilayered constructions with CHT and HA functionalized with catechol groups presented an intrinsic stabilization by catechol interactions and a pH responsiveness that can be useful for a controlled drug delivery.…”
Section: Introductionmentioning
confidence: 99%